Promoting Multiculturalism in Southeast Asia: Is There a Lesson We Can Learn from Canada’s Experience? - Afrianty, Dina (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
This conference was organized with the idea to discuss some crucial issues that challenge global society, in particular, state-government in facing an increasingly globalised world. Society becomes more diverse and complex as a result of infiltration of other cultures and people movements. This situation poses serious challenges for state-government and civil society to ensure that complex social cohesion will not lead to tension and conflict both among members of the society and between the state and the society.DOI: 10.15408/sdi.v18i2.438